Applying endosymbiosis theory: Tourism and its young workers. (September 2019) - Robinson, Richard N.S.; Baum, Tom; Golubovskaya, Maria; Solnet, David J.; Callan, Victor
Abstract: Building on systems theory and its applications in tourism management, we introduce the natural science evolutionary 'endosymbiosis theory' to interpret the inter-dependencies of youth employment and tourism. Tourism organisations are located within a tourism industry or a sub-system, which in turn is bounded within a broader socio-economic ecosystem. We mobilise three classifications of symbiosis - mutualism, commensalism and parasitism to: a) test the analytic utility of this theoretical approach as a means to unpack the young worker and tourism employment relationships, and b) unify hitherto disparate literatures on the youth-tourism employment relationship. In particular, we model the explanatory value of endosymbiosis theory, navigating the ethicalities and moralities of the social sciences, in progressing our understanding of the tourism-young worker intersection. Highlights: Tourism and young workers have a mutualistic relationship regarding employment. Tourism organisations and young workers engage in various forms of symbiosis. Endosymbiosis theory interpretively explains tourism work and youth. Endosymbiosis can be used to frame other relationships in the tourism ecosystem.